Anterior temporal approach for clipping of ruptured basilar tip aneurysms: Surgical techniques and treatment outcomes - Wongsuriyanan, Somkiat (Surg Neurol Int, 2020)
BACKGROUND: Basilar tip (BT) aneurysms are challenging to treat with microsurgical clipping, especially in subarachnoid hemorrhage cases. The anterior temporal approach is one of the surgical approaches for the treatment of aneurysms in this area. The majority of the previous reports on this approach have described unruptured cases. For the ruptured cases assessed in our study, the authors describe the surgical technique, patient characteristics, and surgical outcomes following the use of this technique. METHODS: Fourteen patients with ruptured BT aneurysms who received aneurysm clipping with an anterior temporal approach between December 2015 and August 2019 were retrospectively evaluated. The surgical techniques are described, an illustrative case is shown. RESULTS: The average patient age was 62.2 years (range: 46–78) for ten women and four men. Nine patients (64.3%) were classified as having a poor grade (World Federation of Neurosurgical Societies Grades 4 and 5) at the first presentation. All of the cases demonstrated complete aneurysm obliteration. Good outcomes (mRS 0 to 2) at 6 months were achieved in 58.3% of the patients and in 77.8% of the patients who had a good Glasgow Coma Score after resuscitation before surgery. Postoperative transient oculomotor nerve palsy and thalamic infarctions were detected in six patients (42.9%) and two patients (14.3%), respectively. CONCLUSION: With appropriate case selection, the anterior temporal approach was effective and safe for the clipping of ruptured BT aneurysms.